Gang Organization and Migration/Drugs, Gangs, and Law Enforcement - Skolnick, Jerome H. (1990)
This publication consists of two papers: the first Gang Organization and Migration is a descriptive work based on interviews with California inmates during the Spring and Summer of 1988 and 1989. The second, Drugs, Gangs, and Law Enforcement is more reflective in tone and describes interviews with and observations of law enforcement responses to gang migration